Membangun Cloud Computing Memanfaatkan Google Drive Untuk Meningkatkan Layanan Akademik - Wintolo, Hero; Purnamasari, Derry (SENATIK STT Adisutjipto, 2016)
As one of the products of google, google drive software can be worn and used by computer users who have access to the Internet by using a gmail account. With this account also users of android based smartphone which is also a product of google google drive can access using the equipment. The easier and cheapness of the equipment that is used as cloud computing services to support the academy. This service is an application of academic information used by parents of students to access academic information in the form of academic data. The main source of data from a web server and is designed to upload data automatically academic on google drive, so that data can be read by users who have android smartphone. Academic data that can be seen in the form of pdf format. The software that is made is also tested by utilizing a user who has access to the service academies. The test results showed that the existing data on google drive in accordance with the student registration number is entered and accessed on android smartphone and a value is given using questionnaires and calculated the Likert method was 81.57%.